Trade-off between consumption growth and inequality: Theory and evidence for Germany - Runli Xie (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
This paper examines the structure and evolution of consumption and consumption growth inequality. Once heterogeneous agents relate their neighbors' consumption to their own, consumption volatility and inequality are affected. The relationship predicted between the group average consumption growth and within-group growth inequality was shown as only slightly positive yet significant using survey data from the German Socio- Economic Panel (GSOEP, 1984-2005). Age and household size are crucial for withingroup inequality, as young and/or small households are more sensitive to income and consumption shocks. Large and well-educated households with unskilled jobs have shown surprisingly inferior performance in consumption growth and variance. The data also shows increases of within-group inequality directly after the reunification and the introduction of the euro.
Keywords: E21; D91; D31; D64; 330; consumption inequality; consumption growth; German Socio-Economic Panel; altruism; Verbraucherausgaben; Konsumtheorie; Konsumentenverhalten; Konsuminterdependenz; Soziale Ungleichheit; Theorie; Deutschland